The need for insurance of the food industry in the European Union - Arych, Mykhailo (My University, 2016)
This article examines the factors necessary compulsory insurance of subjects of the food industry in the European Union. Found that functioning single market for insurance services that will improve economic efficiency and market integration, it is necessary to have a common framework that will allow insurers to freely carry out operations in all European Union countries, establish branches and provide services.
Keywords: food; insurer; insured; insurance compensation; харчова промисловість; страховик; страхувальник; страхове відшкодування; пищевая промышленность; страховщик; страховое возмещение; кафедра фінансів